2010
DOI: 10.1002/term.338
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteoblastic differentiation of mesenchymal stem cells seeded in RGD-functionalized PLLA scaffolds and cultured in a flow perfusion bioreactor

Abstract: The present study combines chemical and mechanical stimuli to modulate the osteogenic differentiation of mesenchymal stem cells (MSCs). Arg-Gly-Asp (RGD) peptides incorporated into biomaterials have been shown to upregulate MSC osteoblastic differentiation. However, these effects have been assessed under static culture conditions, while it has been reported that flow perfusion also has an enhancing effect on MSC osteoblastic differentiation. It is clear that there is a need to combine RGD modification of bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 67 publications
(90 reference statements)
2
30
0
Order By: Relevance
“…Common techniques of surface functionalization include chemical modifications via cross-linking polymer chains with bioactive factors, physical modifications via physisorption of the molecules onto the surface, or physical entrapment (Alvarez-Barreto et al, 2011). …”
Section: Control Of Cell Differentiation On Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…Common techniques of surface functionalization include chemical modifications via cross-linking polymer chains with bioactive factors, physical modifications via physisorption of the molecules onto the surface, or physical entrapment (Alvarez-Barreto et al, 2011). …”
Section: Control Of Cell Differentiation On Polymersmentioning
confidence: 99%
“…The positive role of RGD in cell adhesion has been widely demonstrated with various materials, including glasses, hydroxyapatite and polymers (Alvarez-Barreto et al, 2011; De Giglio et al, 2000; Morgan et al, 2008). Support of osteogenic differentiation by the presence of RGD is also dose-dependent (Meinel et al 2004, Shin et al 2005 in Alvarez-Barreto et al 2011).…”
Section: Control Of Cell Differentiation On Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…George et al [2006] demonstrated that the honeycomb collagen sponge is an excellent scaffold for MSC proliferation and osteogenic differentiation. In another study, it was shown that the incorporation of Arg-Gly-Asp (RGD)-functionalized peptides in PLLA scaffolds upregulates osteoblastic differentiation [Alvarez-Barreto et al, 2011]. A study on electrospun poly-epsilon-caprolactone PCL fiber mesh scaffolds with or without the decellularized ECM construct (PCL/ECM) dexamethasone was performed [Thibault et al, 2010].…”
Section: The Role Of Nanomatrices In the Induction Of Osteogenic Diffmentioning
confidence: 99%